Impact of Chocolate Cadmium on Vulnerable Populations in Serbia - Aleksandra Nešić; Milica Lučić; Jelena Vesković; Ljiljana Janković Mandić; Milan Momčilović; Andrijana Miletić; Antonije Onjia (Foods)
Chocolate is one of the most popular and widely consumed confectionery products. However, elevated cadmium (Cd) content in this commodity threatens food safety and human health. It is crucial to monitor the presence of Cd in chocolate and to evaluate its associated health risks. This study assessed the Cd levels in milk and dark chocolates from the Serbian market (n = 155). Cadmium concentrations varied between 0.010 and 0.29 mg/kg. The obtained values were used to evaluate the hazard quotient (HQ) and cancer risk (CR). The estimated weekly intakes (EWIs) were below the tolerable limits for all samples. However, in some samples, the EWI reached 60.9% and 63.5% of the tolerable limit for toddlers and other children, respectively. No health risk was found based on the HQ. On the other hand, based on CR values, all chocolate products can be classified as posing a moderate risk. The Monte Carlo simulation indicated that toddlers and other children were more exposed to non-carcinogenic risk, whereas vegetarians, adults, pregnant women, and other children were more exposed to cancer risk. Sensitivity analysis indicates that body weight, exposure frequency, and ingestion rate are the most influential factors for non-cancer and cancer health risks.